Cost-effectiveness profile, organizational implications and patient preferences on the use of exogenous TSH therapy (Thyrogen®) vs. THW in thyroid residue ablation in Italy - De Danieli, Gianluca; Monari, Fabio; Lazzarini, Renzo; Cipriani, Filippo (Farmeconomia. Health economics and therapeutic pathways, 2016)
BACKGROUND: Radioiodine ablation is an adjuvant procedure used to treat patients with differentiated thyroid cancer. For ablation to be successful, patients must have elevated levels of thyroid stimulating hormone (TSH). This can be achieved by withholding thyroid hormone therapy (endogenous stimulation), or by administration of recombinant human thyroid stimulating hormone (rhTSH; Thyrogen®; exogenous stimulation) to patients in the euthyroid state. AIM: To compare the estimated health benefits, cost and cost-effectiveness of TSH stimulation with and without Thyrogen® in the Italian setting. METHODS: A cost-utility analysis was undertaken to assess the impact of exogenous vs. endogenous TSH stimulation before radioiodine remnant ablation of patients with newly diagnosed, well-differentiated papillary or follicular thyroid cancer who have undergone total or near-total thyroidectomy. A Markov model was developed to simulate treatment costs and health outcomes associated with exogenous and endogenous stimulation in four distinct health states: pre-ablation, ablation, post-ablation, and well/recovery. Treatment was stratified by patients who receive high- and low-activity (30-100 mCi, respectively) in the ablation state. The Italian National Health System perspective was adopted in the base case scenario while the impact of indirect costs was explored in a sensitivity analysis. Costs and quality-adjusted life years (QALY) specific to each health state were estimated, summarized and converted into a corresponding incremental cost-effectiveness ratio (ICER). RESULTS: We calculated a cost-effectiveness ratio of 18,357.18 €/QALY gained whereas the inclusion of indirect cost and accident cost produced reductions of the ICER to € 14,609.51 and € 15,515.26 per QALY, respectively. Finally, all results in the sensitivity analysis are below the lower bound of national and international cost- effective threshold. CONCLUSION: Thyrogen® represents a cost-effective option for patients with differentiated thyroid cancer who underwent total or near-total thyroidectomy in Italy. Our findings are consistent with other cost-utility analyses.